Welsh Women Teachers and the Women’s Movement in South Wales (1870-1928) - Joelle Gorno (Revue Française de Civilisation Britannique)
For centuries, Wales was subjected to an Anglo-centric narrative, its own history being merged with that of England. Women across Wales have equally been the object of this neglect. Welsh women teachers during the latter half of the nineteenth century through to the early twentieth century proved to be more than simply educators. Driven by the search for equality, many of these women became activists in the women’s movement. This paper will explore the different ways in which these Welsh teachers participated in public life, whether in the suffrage movement or in local politics, in order to achieve this equality.